ADMINISTRASI KETENAGAKERJAAN DI KOTA PEKANBARU: (Studi Perlindungan Tenaga Kerja Wanita) - Sri Maulidiah (UIR Press, 2018)
This paper is motivated by still many problems associated with employment in the city of Pekanbaru, especially women workers. The phenomenon that is seen on the issues of women's employment, among others; the number of female labor force continues to increase every year, there are many companies in the use of female labor is not in accordance with the legislation, there are still many women are employed at night, there are still many rights of women workers which are not given such a right to breastfeeding, menstruation, and so forth, and there are still many heard the cases of sexual harassment of women workers, and there are many women workers are employed minors by companies, and other problems. Resulting in discrimination against female workers in finding employment and occupation. Therefore the article wants to know how the government protection for these women workers. The government has issued Law of the Republic of Indonesia Number 13 of 2003 on Labour, which also clearly and Resolute has been protecting the rights of these women workers. Pekanbaru City Government has also been instrumental to the protection of women workers is through oversight of companies that use tenga this work, and provide sanctions against companies that do not implement the Employment Act is in the use of women workers in the company. Pekanbaru City Government has also provided counseling to women workers and corporate users of the Employment Act. Nevertheless suggested to the Municipality to be more intensive in protecting women's labor, so that a variety of issues related to women's labor force can be minimized, and the female labor force can be enabled through the protection of the female labor force.